The use of information in policy processes: Epistemological and decisional tensions in the National Policy of Educational Evaluation in Mexico - Valladares, Liliana (Education Policy Analysis Archives, 2019)
One of the objectives of the National Policy for Educational Evaluation in Mexico (PNEE) is to support the design of educational policies based on the information provided by the evaluation results. This paper argues that the use of information in policy processes is undergoing a strong debate about the role of knowledge in public decisions. This debate is addressed through the description of five tensions that are presented in the epistemological and decisional dimensions associated with the policy cycle. It is proposed that the analysis and reflection around these tensions can enrich the understanding of the evidence-based policy approach and contribute, with new theoretical elements, to the design of the actions and measures proposed by